BENEFITS OF INCORPORATING COMMON PHRASES AMONG LEARNERS IN NON-LINGUISTIC EDUCATIONAL SETTINGS. (International journal of artificial intelligence, 2025)
This article explores the advantages of using popular expressions among students in non-linguistic educational institutions, such as engineering, medical, and business schools. It highlights how colloquial language, including idioms, slang, and catchphrases, fosters social interaction, group cohesion, and creativity. The article discusses how such expressions enhance communication skills, promote cultural awareness, and create a relaxed learning environment, ultimately contributing to a more engaging and effective educational experience. It also emphasizes that the integration of popular expressions helps students develop better networking and collaboration abilities, facilitating both academic success and professional growth.